2023
DOI: 10.1038/s41598-023-42753-3
|View full text |Cite
|
Sign up to set email alerts
|

Improved YOLOv5-based for small traffic sign detection under complex weather

Shenming Qu,
Xinyu Yang,
Huafei Zhou
et al.

Abstract: Traffic sign detection is a challenging task for unmanned driving systems. In the traffic sign detection process, the object size and weather conditions vary widely, which will have a certain impact on the detection accuracy. In order to solve the problem of balanced detecting precision of traffic sign recognition model in different weather conditions, and it is difficult to detect occluded objects and small objects, this paper proposes a small object detection algorithm based on improved YOLOv5s in complex we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Poor environmental conditions also affect the quality of the camera images, making object detection harder. However, research in the field of autonomous driving has shown that additional training data and improvements in the model architecture allow the model to better generalize and significantly improve object detection accuracy in these conditions [15,16].…”
Section: Related Workmentioning
confidence: 99%
“…Poor environmental conditions also affect the quality of the camera images, making object detection harder. However, research in the field of autonomous driving has shown that additional training data and improvements in the model architecture allow the model to better generalize and significantly improve object detection accuracy in these conditions [15,16].…”
Section: Related Workmentioning
confidence: 99%